Muscle vs. Heart: A Comprehensive Review of Anabolic Steroid-Induced Cardiovascular Risks - Muchukota Sushma; Navitha G A; Subikchya K; Salim AL Abdullah; Shobha Rani R.H (International Journal of Toxins and Toxics, 2026)
Anabolic-androgenic steroids (AAS) are widely used by athletes and bodybuilders to enhance muscle mass and performance. However, their misuse is associated with serious and often underrecognized cardiovascular risks. Despite their popularity, particularly among young adults, the long-term consequences of AAS abuse on cardiovascular health remain insufficiently explored in the literature. This review aims to: 1. Analyze the cardiovascular implications of AAS use. 2. Elucidate the molecular and physiological mechanisms contributing to AAS-induced cardiovascular damage. 3. Identify existing research gaps, including the need for long-term studies, dose-response evaluations, and analysis of demographic and psychological variables. 4. Propose evidence-based preventive and intervention strategies to mitigate cardiovascular risk in AAS users. A comprehensive review of peer-reviewed literature was conducted using major scientific databases, focusing on studies related to AAS-induced cardiovascular effects. Articles were selected based on relevance, recency, and methodological quality, with particular emphasis on mechanistic insights, epidemiological data, and clinical outcomes. Findings reveal that AAS misuse contributes to various forms of cardiovascular pathology, including left ventricular hypertrophy, endothelial dysfunction, accelerated atherosclerosis, arrhythmias, and increased risk of sudden cardiac death. Structural and functional cardiac alterations are often irreversible and exacerbated by prolonged and high-dose steroid use. Significant gaps remain in understanding dose-response relationships, age and gender-related susceptibility, and the psychosocial motivations behind AAS abuse. While AAS may enhance physical performance, their cardiovascular risks are substantial and largely under recognized, especially among young recreational users. Regular medical monitoring, public education, policy regulation, and the development of interdisciplinary treatment models are urgently needed. Long-term cohort studies and targeted awareness campaigns are essential to addressing this emerging public health concern.
Keywords: Anabolic steroids; Anabolic-androgenic steroids (AAS); Arrhythmia; Atherosclerosis; Cardiac remodelling; Cardiovascular toxicity; athletes